2022
DOI: 10.32859/era.24.20.1-22
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobiological Uses of Plant Species among the three Ethnic Communities in the Administrative District (Kupwara) of Jammu and Kashmir-India: A cross-cultural Analysis

Abstract: Introduction: In the valley of Kashmir-India, use of flora is not only prioritized over fauna species to get against health disorders but plays a vital role in the cultural aspects. The uses of herbs, particularly those that have a scientific basis as remedy of minor illnesses are progressively appreciated across the modern world.Methods: The present study was conducted from March 2019 to August 2021 for the collection of medicinally important plants and related traditional knowledge in the frontier administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Asteraceae were the most prominent family for treating MSDs among the North Waziristan community, which agrees with other ethnomedicinal research around the world [11,26,27]. The reason behind the dominance of the Asteraceae family is that the family members are familiar for aromatic quality and are easily accessible in wild nature, or might be due to its widespread distribution and richness in the study area [28,29].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Asteraceae were the most prominent family for treating MSDs among the North Waziristan community, which agrees with other ethnomedicinal research around the world [11,26,27]. The reason behind the dominance of the Asteraceae family is that the family members are familiar for aromatic quality and are easily accessible in wild nature, or might be due to its widespread distribution and richness in the study area [28,29].…”
Section: Discussionsupporting
confidence: 84%
“…The use of medicinal plants by indigenous communities to treat various disorders is a practice that has been passed down through many generations of human evolution [9]. Roughly 85% of the global population residing in developing countries relies solely on traditional medicinal plants for their healthcare needs [10,11]. Ethnic communities residing in proximity to forested regions depend on the collection of medicinal plants from the wild for their primary healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Fodder is mostly collected in the summer to autumn in the study area and it's dried and stored for winter. Similar results were reported by [15,55,56]. Fuelwood plays an important role in the study area; some of the important fuelwood plants collected by the people of the study area were Ailanthus altissima, Abies pindrow, Berberis lycium, Cedrus deodara, Parrotiopsis jacquemontiana and Pinus wallichiana.…”
Section: Other Ethnobotany Usessupporting
confidence: 89%
“…The plants with higher citations in the Pahari community included Plantago major, Viola odorata, Cannabis sativa, Oxalis acetosella, and Bistorta amplexicaulis. Khoja et al [55] also reported Aconitum heterophyllum, Malva neglecta, and Polygonatum bi orum are highly utilized plants for the Gujjar community in Kashmir Himalaya. Similarly, Ridwan et al [61] documented Podophyllum hexandrum and Diplazium maximum in Pahari community in Rajouri district.…”
Section: Classi Cation Of Cultural Plantsmentioning
confidence: 99%
“…A detailed description of the therapeutic flora used to treat dermatological ailments is recorded in Table 2 . These plant species were known for phytochemicals like alkaloids, phenols, terpenes, flavonoids, lactins, and saponins which might explain their efficacy in treating dermatological disorders [ 21 , 22 , 23 ]. In the study area, people mostly visit the high altitudes in the summers along with their cattle, where no medical facilities are available.…”
Section: Resultsmentioning
confidence: 99%